2021
DOI: 10.1111/ijfs.15312
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the rheological and technological properties of biscuits with different levels of replacement of wheat flour by rice and azuki bean flour

Abstract: A mixture design was used to evaluate the effect of replacing (0 to 100%) wheat flour (WF) with wholegrain azuki bean (WABF) and rice (RF) flours on the biscuits quality. High proportions of WABF increased diameter and decreased thickness, whereas WF affected inversely and RF intermediate. The WF biscuit specific volume was 17% greater than that of the dough, and the WABF and RF biscuits were 5 and 13% smaller, respectively. The WABF biscuit hardness was 26.25 N, close to WF (28.14 N), and higher than RF (7.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These results were opposite to those obtained by Zhao et al (2019) and Silky and Tiwari (2014), and in agreement with Mancebo et al (2016), possibly protein content associated with the presence of NaCl may have prevented the increase in REI value. Silva et al (2021) when using a sweet biscuit formulation found an increase in REI, this may be associated with the high sucrose content, which makes the dough more fluid during baking, favoring the increase in the biscuit diameter.…”
Section: Resultsmentioning
confidence: 96%
“…These results were opposite to those obtained by Zhao et al (2019) and Silky and Tiwari (2014), and in agreement with Mancebo et al (2016), possibly protein content associated with the presence of NaCl may have prevented the increase in REI value. Silva et al (2021) when using a sweet biscuit formulation found an increase in REI, this may be associated with the high sucrose content, which makes the dough more fluid during baking, favoring the increase in the biscuit diameter.…”
Section: Resultsmentioning
confidence: 96%
“…The widespread popularity of bakery items worldwide has led to a significant increase in production due to their affordability, diverse tastes and textures, attractive packaging, and extended shelf life for convenient marketing (Patel et al, 1996;Silva et al, 2021). Millets offer superior fiber content and micronutrient profiles when incorporated into bakery products, presenting a strong opportunity for millets to penetrate the baking industry with various value-added products (Verma & Patel, 2013).…”
Section: Millet-based Food Products 1 Baked Productsmentioning
confidence: 99%
“…Additionally, the content of pea protein ranges from 20% to 25% (Lu et al ., 2019), the protein content of yellow pea is about 15–25% (Luo & Koksel, 2020), and the protein content of chickpea ranges from 18% to 29% (de Camargo et al ., 2019; Sofi et al ., 2020c). Besides the protein content of pigeon pea is 20–22% (Anitha et al ., 2020), the content of cowpea protein ranges from 18% to 35% and lupin protein ranges from 35% to 40% (Melini et al ., 2017), and Azuki beans are 21.4–24.5% protein (Silva et al ., 2021). Moreover, the protein content of Bambara groundnut ranges from 15% to 27% (Oyeyinka & Oyeyinka, 2018), lentils are about 31% protein (Atudorei & Codină, 2020), and the content of soybean protein is between 30 and 50% (Urade, 2019).…”
Section: Nutritional Properties and Physiological Functions Of Legume...mentioning
confidence: 99%